The ED50 and ED95 of Prophylactic Norepinephrine for Preventing Post-Spinal Hypotension During Cesarean Delivery Under Combined Spinal-Epidural Anesthesia: A Prospective Dose-Finding Study - Xu, Wenping; Drzymalski, Dan Michael; Ai, Ling; Yao, Hanqing; Liu, Lin; Xiao, Fei (Frontiers in Pharmacology, 2021)
Background: Hypotension commonly occurs with spinal anesthesia during cesarean delivery. Norepinephrine is an alternative to phenylephrine which can be used to prevent or treat hypotension, with better maintained cardiac output and less bradycardia. However, an appropriate initial prophylactic infusion dose of norepinephrine remains unclear. The aim of this study was to describe the dose-response relationship of prophylactic norepinephrine infusion during cesarean delivery under combined spinal-epidural anesthesia. Methods: We performed a prospective, randomized, double-blinded dose-finding study. One hundred patients undergoing elective cesarean delivery were randomly assigned to receive an infusion of norepinephrine at 0, 0.025, 0.05, 0.075 or 0.1 µg/kg/min initiated immediately after intrathecal injection of 10 mg bupivacaine combined with 5µg sufentanil. An effective dose was considered when there was no hypotension (systolic blood pressure <90 mm Hg or <80% of baseline) during the time period from injection of intrathecal local anesthetic to delivery of the neonate. The primary aim was to determine the dose-response relationship of norepinephrine to prevent spinal anesthesia-induced hypotension. The median effective dose (ED50) and 95% effective dose (ED95) for norepinephrine were calculated utilizing probit analysis. Results: The proportion of patients with hypotension was 80%, 70%, 40%, 15% and 5% at norepinephrine doses of 0, 0.025, 0.05, 0.075 and 0.1µg/kg/min, respectively. The ED50 and ED95 were 0.042 (95% CI, 0.025 to 0.053) µg/kg/min and 0.097 (95% CI, 0.081 to 0.134) µg/kg/min, respectively. There were no differences in the Apgar scores (P = 0.685) or umbilical arterial pH (P = 0.485) measurements of the newborns among the treatment groups. Conclusions: A norepinephrine infusion of 0.1µg/kg/min as an initial starting dose was effective for the prevention of spinal-induced hypotension.